Exploring the spatial configurations of home gardens in Benin. - Gbedomon, Rodrigue Castro; ASSOGBADJO, ACHILLE EPHREM; SALAKO, Kolawolé Valère; FANDOHAN, ADANDE BELARMAIN; Glèlè kakaï, Romain (My University, 2016)
Although home gardeners could logically install plant species at different places around their homesteads, there is no quantitative evidence of how home gardens (HGs) are spatially configured and how these spatial configurations (SCs) discriminate plant species within HGs. Using spatial position analysis with respect to homestead and garden inventories, this paper explores the SCs of 360 HGs and assesses their constituent species as well as their prevalence across seasons, agro-ecological zones (AEZs) and phyto-geographical districts (PDs) in Benin. The association between SC and species composition was tested using correlation coefficients and Jaccard dissimilarity. A non-metric multidimensional scaling and a canonical discrimination analysis were performed to detect SCs discriminating AEZ and PDs. Relative frequencies of each SC were calculated per PD and displayed on the Benin map using ArcGIS 10.0 software. Eight SCs were distinguished, and 90.55% of HGs contained at least two SCs. Except for yards, SCs shared no or few species. The occurrence and prevalence of SCs varied across AEZs and PDs. Because HGs have multiple SCs and dynamic components, their size and shape may not always be objective indicators in the HG horizontal structure analysis.
Keywords: Spatial configurations; Home gardens; Species composition; West Afric